Situation Report: Czechoslovakia, 28 February 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Commemorative CPCS CC Plenum Celebrations of the February 1948 Coup Relations with Hungary